VARIASI SERAT GELAS PADA PAPAN SEMEN DENGAN MORTAR BUSA: VARIASI SERAT GELAS PADA PAPAN SEMEN DENGAN MORTAR BUSA - Rikki Sofyan Rizal; Pratikto; Anni Susilowati (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
Foam mortar is a composite material consisting of a mixture of foaming fluid, cement, sand and water. Foam mortar technology is currently being developed and can be an option for cement board mixtures that have a light weight. Foam mortar cement board is one such product. Glass fiber has a fairly high tensile strength. This makes glass fiber potential as a reinforcing material in the manufacture of cement boards. The fiberglass used is fiber with a size of 31 x 31 cm and a thickness of 0.2-0.6 mm. The purpose of this study was to obtain a cement board with a small or light density, obtain the characteristics of a cement board with foam mortar and the addition of glass fiber, and obtain the optimum content of glass fiber for maximum flexural strength and still meet the requirements of SNI 15-0233-1989. The mixture ratio is 1 PC : 1.2 PS : 0.5 foam with FAS 0.47 and variations in glass fiber content of 0%, 8%, 16%, 23%, and 31% fiber by weight of cement. The results of the analysis show that the more glass fiber used can reduce the density, increase the water content, water absorption, and increase the flexural strength up to 10 times. The highest flexural strength was found in the variation of 31% fiber and the lowest was 0% fiber with values ??of 14,931 kg/cm2 and 1,195 kg/cm2. The addition of glass fiber also increases the nailing ability of the foam cement mortar board and complies with the SNI 15-0233-1989 standard. Key words : Cement Board; Foam Mortar; Fiberglass.